2021
DOI: 10.1021/acsami.0c22915
|View full text |Cite
|
Sign up to set email alerts
|

Well-Dispersed Garnet Crystallites for Applications in Solid-State Li–S Batteries

Abstract: A uniform ceramic tape of well-dispersed garnet-type Li6.4La3Zr1.4Ta0.6O12 particles (LLZTO) with a high solid content of 70 wt % is prepared as an electrolyte in solid-state Li–S batteries. The use of appropriate dispersants is crucial for achieving fine dispersion and uniform distribution of LLZTO particles in the ceramic tape. This leads to improved surface flatness and mechanical strength of the ceramic tape. Moreover, the ionic conductivity increases remarkably at the same time from 10–5 to 10–4 to 10–4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…Cell energy density evaluation. (a–c) Comparison of initial discharge capacity and energy density in this work with state-of-the-art published results. ,, …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Cell energy density evaluation. (a–c) Comparison of initial discharge capacity and energy density in this work with state-of-the-art published results. ,, …”
Section: Resultsmentioning
confidence: 86%
“…For this work with a high sulfur mass loading on a planar surface, we demonstrated that, with our thin bilayer Ta-LLZO design, an energy density of 639 W h/L and 134 W h/kg was achieved at 0.03C at RT based on the high initial discharge capacity of 1307 mA h/g (Figure a,b, see Table S3 for detailed calculation and Table S4 for detailed comparison). This value is beyond that of state-of-the-art garnet-type hybridized Li–S batteries with a sulfur cathode on a planar garnet surface, which have limited energy densities of less than 400 W h/L and 100 W h/kg (Figure ), mainly due to the thick electrolyte and low sulfur mass loading. ,, …”
Section: Resultsmentioning
confidence: 89%
“…However, PVDF-HFP is unstable under a typical cycling voltage (>4 V) of Li-ion batteries. , This shortcoming could be alleviated by blending ceramic fillers such as TiO 2 , SiO 2 , Al 2 O 3 , and BaTiO 3 and solid-state electrolyte particles including Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP) and Li 7 La 3 Zr 2 O 12 (LLZO) with PVDF-HFP. Here we have selected LLZTO to fabricate our flexible SE composites due to its high mechanical rigidity and Li + attracting characteristic. , …”
Section: Resultsmentioning
confidence: 99%
“…Here we have selected LLZTO to fabricate our flexible SE composites due to its high mechanical rigidity 54 and Li + attracting characteristic. 55,56 FEA numerical simulations (COMSOL Multiphysics 6.0) were conducted to analyze the difference in the Li + migration trend and concentration distribution for the case where the SE separator and CNT anode framework were applied compared to the case where the commercial PP separator and 2D Li metal anode were used. Detailed 2-dimensional geometry domain information for each separator|anode pair is summarized in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…(d) Conductivity of PEO-LiTFSI-LLZO (0-50wt%). (e) Schematic of Li-ion pathways in PEO-LiTFSI-LLZO (5wt%), PEO-LiTFSI-LLZO (20wt%) and PEO-LiTFSI-LLZO (50wt%), and corresponding 6 Li NMR spectra [51] A c c e p t e d https://engine.scichina.com/doi/10.1360/TB-2021-1078 除了无机纳米颗粒在聚合物基体中的含量外,纳米颗粒的粒径也被证明对聚合物基 固 体 电 解 质 的 离 子 电 导 有 影 响 。 Zhang 等人 [62] 比较了基于纳 米 级 和 微 米 级 Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO)填料的 PEO 基固体电解质的离子导电性, 含有纳米级 LLZTO 颗粒 (~40 nm) 的复合电解质膜的室温电导率 (2.1 × 10 -4 S cm -1 ) 比微米级填料 (10 µm) 的电导率(3.8 × 10 −6 S cm −1 )大近两个数量级。这是由于纳米和微米颗粒之间比表面积 的差异引起了渗流效应的差异。因上,一般选择纳米级的填料与聚合物复合制备固体电 解质。此外,纳米颗粒在聚合物基体中分布的均匀性对电解质的离子电导率也有显著影 响 [63,64] 。Langer 等人 [63] 制备了成分固定为 10vol% LLZO、但填料分布不同的 PEO 基聚 合物基复合固体电解质,该复合电解质在~70℃下有相似的离子电导率,但是当组装…”
unclassified